Pricing strategy at the local salt industry institutional structure of East Java, Indonesia - Siti Komariyah; Lilis Yuliati; Mustofa Mustofa; Nely Supeni (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
This study aims to create a strategy to increase local salt prices in the East Java Region. The analytical method used in this study is the Analytical Hierarchy Process (AHP) method to create a strategy to increase local salt prices in East Java. The analysis reveals that the problems in the field can be classified into three groups of problems, namely salt quality problems, marketing problems, and problems in financing. Based on these problems, the main policy alternatives we make are product standardization, market regulation, and financial regulation.